The role of primary care physicians in enabling validation of a patient’s ability to make legal statements and express a last will - Trnka, Jakub; Drobnik, Jarosław; Susło, Robert (Family Medicine & Primary Care Review, 2017)
The expression of a last will is legally invalid when the will-maker was in a state preventing him or her from making a decision, or expressing will, in a conscious or independent way; this could occur due to psychiatric disorders, mental retardation, or any other mental activity disturbance, even temporary. There are many problems with medical opinions concerning the validity of last wills. Medical staff play an important and law-rooted role in providing valuable evidence in such cases. The forensic medical literature was searched for topics related to evaluations of last will and testament. Forensic opinions issued by the Forensic Medicine Department, Wrocław Medical University, Poland, in years 2006–2016 were also examined for cases illustrating the role of physicians and medical files in the legal evaluation of contested wills. This allowed us to conclude that mental status alterations that prevent patients from making last wills in a legally valid way can result from psychiatric or somatic disorders that negatively influencing the level of consciousness. Medical files are a highly valuable and trustworthy source of evidence – especially in the parts authored by medical staff in frequent contact with patients, which includes primary and palliative care physicians or nurses. It is necessary that these files contain remarks on the patient’s behavior and ability to function in a home environment, as well as information shared by the patient’s relatives. It is crucial that any drugs prescribed and their doses are recorded, and that the actual drugs administered to the patient are also noted.